Planeamiento estratégico y la gestión pública en la Municipalidad Distrital de San Juan Bautista Loreto 2022 - Alván Méndez, Shirley Vanessa (2024)
The purpose of this final report is to diagnose the relationship between strategic planning and public management in the District Municipality of San Juan Bautista 2022. The study has been descriptive-correlational and non experimental in design. Opting for a population of 460 workers, taking 210 as a sample, a survey accompanied by a questionnaire was used to collect the data. The results show that strategic planning is rated as regular (28%), this is because sometimes policies are established that direct the adequate development of activities; Just as strategic planning has sometimes made it easier to forecast unexpected events to make correct decisions. For its part, public management is regular (29%) since the municipality sometimes applies the strategic plan for the effectiveness of its management; and adequately manages marketing services by verifying the existence of operating licenses. Concluding that there is a strong positive correlation between strategic planning and public management, corroborated by a coefficient of rho=0.846 and a sig of 0.000. Likewise, the elements of planning have a coefficient and significance of (r=.814; p=0.000), and the advantages of planning have a coefficient and significance of (r=0.769; p=0.000), both of which are significantly related to the Public Management.